ADIPOQ polymorphisms and haplotypes affect circulating adiponectin levels and their association with gestational hypertension and preeclampsia - Fróes de Castro, Ricardo Nodari; Pereira, Daniela Alves; de Oliveira Cruz, Juliana; Palei, Ana C.; Rangel Machado, Jackeline S.; Cavalli, Ricardo C.; Tanus-Santos, Jose E.; Sandrim, Valéria Cristina; Luizon, Marcelo Rizzatti (Frontiers in Physiology, 2026)
IntroductionImbalance of adipocytokines has been implicated in endothelial dysfunction in hypertensive disorders of pregnancy (HDP). Adiponectin is an adipocytokine that regulates metabolism, insulin sensitivity, and inflammation, and increased adiponectin levels have been associated with mortality in subjects with cardiovascular diseases. Adiponectin also plays a role in trophoblast invasion during placental development. ADIPOQ gene has polymorphisms that modulate adiponectin levels and are linked to several diseases, including gestational hypertension (GH) and preeclampsia (PE). However, no previous study has examined whether ADIPOQ SNPs and haplotypes affect adiponectin levels in HDP.ObjectivesWe assessed and compared plasma adiponectin levels among healthy pregnant (HP, n = 182), GH (n = 121), and PE (n = 133) women, and examined whether ADIPOQ SNPs rs266729, rs2241766 and rs1501299, and their haplotypes are associated with susceptibility to HDP; and whether these polymorphisms and haplotypes affect adiponectin levels in HP, GH and PE.Materials and MethodsAdiponectin concentrations were determined using the Human Adiponectin ELISA kit. Genotypes were determined by Taqman allele discrimination assays. Haplotype frequencies were estimated using Haplo. stats. Multiple logistic/linear regression analyses were adjusted for selected covariates.ResultsPlasma adiponectin levels were higher in PE than in HP, including when patients were stratified by body mass index. Regarding rs266729 (C>G) SNP, the GG genotype was associated with risk for GH, and the CG genotype may protect against PE. PE patients carrying the CG and GG genotypes showed higher adiponectin levels than their CC counterparts. The ‘G,T,G’ haplotype showed higher adiponectin levels in PE than in HP, and the ‘C,T,T’ haplotype may protect against GH.ConclusionOur novel findings indicate that ADIPOQ polymorphisms and haplotypes may affect circulating adiponectin levels and the susceptibility to GH and PE.